The effect of acoustic radiation force on osteoblasts in cell/hydrogel constructs for bone repair - Veronick, James (Exp Biol Med (Maywood), 2016)
Ultrasound, or the application of acoustic energy, is a minimally invasive technique that has been used in diagnostic, surgical, imaging, and therapeutic applications. Low-intensity pulsed ultrasound (LIPUS) has been used to accelerate bone fracture repair and to heal non-union defects. While shown to be effective the precise mechanism behind its utility is still poorly understood. In this study, we considered the possibility that LIPUS may be providing a physical stimulus to cells within bony defects. We have also evaluated ultrasound as a means of producing a transdermal physical force that could stimulate osteoblasts that had been encapsulated within collagen hydrogels and delivered to bony defects. Here we show that ultrasound does indeed produce a measurable physical force and when applied to hydrogels causes their deformation, more so as ultrasound intensity was increased or hydrogel stiffness decreased. MC3T3 mouse osteoblast cells were then encapsulated within hydrogels to measure the response to this force. Statistically significant elevated gene expression for alkaline phosphatase and osteocalcin, both well-established markers of osteoblast differentiation, was noted in encapsulated osteoblasts (p < 0.05), suggesting that the physical force provided by ultrasound may induce bone formation in part through physically stimulating cells. We have also shown that this osteoblastic response is dependent in part on the stiffness of the encapsulating hydrogel, as stiffer hydrogels resulted in reducing or reversing this response. Taken together this approach, encapsulating cells for implantation into a bony defect that can potentially be transdermally loaded using ultrasound presents a novel regenerative engineering approach to enhanced fracture repair.